2012
DOI: 10.1177/0194599812451438a248
|View full text |Cite
|
Sign up to set email alerts
|

Oral Itraconazole as an Adjunct to Steroids in AFRS

Abstract: ORAL PRESENTATIONSand no negative secondary effects were observed. Partial return to initial position of the nasal septum was observed in 20% of the patients 2 or 3 weeks after LSC. A 2-year followup did not show any posterior alterations in the position of the nasal septum. Only 5% of the patients who underwent LSC showed no improvement of nasal breathing. The positive results were obtained in 95% of the treated patients.Conclusion: LSC is a new non-invasive procedure with many advantages over the traditional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Seiberling and Wormald 18 and Panda et al 21 also show a similar result of improved cavity conditions in established recurrences with the use of postoperative itraconazole in AFS. Rains and Mineck 17 retrospectively evaluated 137 cases of recurrent disease in which patients were given high doses of itraconazole until the patients showed disappearance of the disease in nasal endoscopy and had found that once disappearance of disease in nasal endoscopy was achieved, 50.3% showed recurrence after average duration of 10.8 months of follow-up.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Seiberling and Wormald 18 and Panda et al 21 also show a similar result of improved cavity conditions in established recurrences with the use of postoperative itraconazole in AFS. Rains and Mineck 17 retrospectively evaluated 137 cases of recurrent disease in which patients were given high doses of itraconazole until the patients showed disappearance of the disease in nasal endoscopy and had found that once disappearance of disease in nasal endoscopy was achieved, 50.3% showed recurrence after average duration of 10.8 months of follow-up.…”
Section: Discussionmentioning
confidence: 69%
“…Topical amphotericin B in the form of nasal spray and nasal lavage in the postoperative period has been shown to produce symptomatic improvement but failed to show improvement in nasal endoscopic or radiologic scores. 15,16 Rains and Mineck, 17 Seiberling and Wormald, 18 Chan et al , 19 Gupta et al , 20 Panda et al 21 in their studies have proven the role of itraconazole in AFS as a postoperative adjunct, which indicates that itraconazole is efficacious in delaying recurrences. Itraconazole has also been used in allergic bronchopulmonary aspergillosis and has been shown to reduce maintenance steroid requirements.…”
mentioning
confidence: 97%